Cholesterol Treatment Guidelines - Laura Davisson; Mohanad Bakkar (Association of American Medical Colleges, 2015)
Abstract This team-based learning resource was designed to provide an update on blood cholesterol management based on the latest 2013 American College of Cardiology/American Heart Association guidelines. It is composed of a PowerPoint presentation with interactive cases and a self-assessment quiz. It can be used by medical educators alone or as a supplement to a clinical rotation for primary care residents, internal medicine residents, or medical students. The purpose is to teach and evaluate participants about how to approach, manage, and implement new guidelines on blood cholesterol (hyperlipidemia). This resource has been well received so far at our institution in the third-year medicine clerkship. It has only been used three times (once per each 8-week block) because the national guidelines were released during the last academic year. Lectures were not supposed to change mid-year so these revamped teaching materials were not fully implemented until July 2014.